2016
DOI: 10.1039/c6cp05446c
|View full text |Cite
|
Sign up to set email alerts
|

ZnGeSb2: a promising thermoelectric material with tunable ultra-high conductivity

Abstract: First principles calculations predict the promising thermoelectric material ZnGeSb with a huge power factor (Sσ/τ) on the order of 3 × 10 W m K s, due to the ultra-high electrical conductivity scaled by a relaxation time of around 8.5 × 10 Ω m s, observed in its massive Dirac state. The observed electrical conductivity is higher than the well-established Dirac materials, and is almost carrier concentration independent with similar behaviour of both n and p type carriers, which may certainly attract device appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…First-principles calculations suggested competitive thermoelectric performance for selected chalcopyrites, , including for ZnGeSb 2 . In these chalcopyrites, band degeneracies are closely related to the so-called tetragonality, which depends on the ratio of the lattice parameters, specifically c /(2 a ).…”
Section: Introductionmentioning
confidence: 99%
“…First-principles calculations suggested competitive thermoelectric performance for selected chalcopyrites, , including for ZnGeSb 2 . In these chalcopyrites, band degeneracies are closely related to the so-called tetragonality, which depends on the ratio of the lattice parameters, specifically c /(2 a ).…”
Section: Introductionmentioning
confidence: 99%
“…6,13 For this reason, much effort is currently being expended on the search for new more efficient thermoelectric materials. [14][15][16][17] Meanwhile, possibilities for enhancing the performance of existing materials are also being explored. For example, a number of theoretical studies have indicated that with the use of various external factors, such as applied pressure or stress, one can attain very high ZT magnitudes in existing thermoelectric materials.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ZnGeSb 2 as a trivial insulator in their native state in the ref 39 . However there are contradictory report 56 which shows some kind of massive Dirac states at the parent phase. But in the both studies the detailed study of the topological properties and quantities are still far from being investigation.…”
Section: Introductionmentioning
confidence: 95%